Plastic Recycling as a Waste Management Technology and Its Impact on Public Health: A Review - Pratiwi, Inggi; Agresiya, Alda; Yani, Sifa; Triana, Rahma (Journal of Epidemiology and Health Science, 2026)
Background: Plastic is a type of waste that cannot be decomposed by itself (non-biodegradable) which offers many benefits, but also has a big negative impact if not handled properly, especially in terms of daily activities. Objective: This study is to explore the various technologies that have been developed for plastic recycling and evaluate the effectiveness, benefits, and drawbacks of each technology, as well as their impact on public health. Methods: This study used a Systems Literature Review (SLR) approach to collect and analyze online sources. Simpler methods, such as ecobrick -making, have proven effective in empowering communities, while modern technologies offer greater efficiency despite challenges related to cost, infrastructure, and potential new pollution. Results: An evaluation of 25 selected journals and articles revealed that recycling technology has significant potential to reduce plastic waste accumulation and raise public awareness of the importance of waste management. This research demonstrates the success of methods such as ecobricks in empowering communities to transform plastic waste into useful products. Conclusion: Ineffective plastic waste management poses serious environmental and public health problems. Therefore, a comprehensive management strategy is needed, utilizing various recycling techniques, including mechanical, chemical, and biological ones. Successful plastic waste management depends on active community involvement, stable policy support, and improved inter-agency coordination. Keywords: Plastic recycling, waste management, recycling technology, public health, environmental impact.